The 2023 report of the Lancet Countdown on health and climate change: the imperative for a health-centred response in a world facing irreversible harms - Romanello, Marina; Napoli, Claudia di; Green, Carole; Kennard, Harry; Lampard, Pete; Scamman, Daniel; Walawender, Maria; Ali, Zakari; Ameli, Nadia; Ayeb-Karlsson, Sonja; Beggs, Paul J; Belesova, Kristine; et al. (The Lancet (British edition), 2023)
In 2022, the Lancet Countdown warned that people's health is at the mercy of fossil fuels and stressed the transformative opportunity of jointly tackling the concurrent climate change, energy, cost-of-living, and health crises for human health and wellbeing. Harnessing the rapidly advancing science of detection and attribution, new analysis shows that over 60% of the days that reached health-threatening high temperatures in 2020 were made more than twice as likely to occur due to anthropogenic climate change (indicator 1.1.5); and heat-related deaths of people older than 65 years increased by 85% compared with 1990–2000, substantially higher than the 38% increase that would have been expected had temperatures not changed (indicator 1.1.5). [...]those countries that have historically contributed the least to climate change are bearing the brunt of its health impacts—both a reflection and a direct consequence of the structural inequities that lie within the root causes of climate change. The 2022 Lancet Countdown report highlighted the opportunity to accelerate the transition away from health-harming fossil fuels in response to the global energy crisis.